2006
DOI: 10.1038/sj.jid.5700451
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Levels in Normal and Previously Irradiated Human Skin as Assessed by EF5 Binding

Abstract: The oxygen status of skin is a controversial topic. Skin is radiosensitive, suggesting it is well-oxygenated. However, it can be further sensitized with nitroimidazole drugs, implying that it is partially hypoxic. Skin oxygen levels are difficult to measure with either electrodes or the hypoxia-monitoring agent (3)H-misonidazole. For the latter, binding has previously been reported to be high in murine skin, but this could be attributed to either non-oxygen-dependent variations in nitroreductase activity, drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
106
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 114 publications
(113 citation statements)
references
References 41 publications
6
106
0
Order By: Relevance
“…It should be noted however, that although the number of patients presented herein is small (n=22), it is similar to studies using the Eppendorf needle electrode Intriguing observations from this study include the varied patterns of EF5 binding in HNSCC. Type 1 binding pattern is most similar to EF5 binding in sarcomas and brain tumors 24,25 and Type 2 binding is most reminiscent of the EF5 binding patterns described in normal human skin 30 . Using pimonidazole, similar patterns of binding have been reported 45,46 .…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…It should be noted however, that although the number of patients presented herein is small (n=22), it is similar to studies using the Eppendorf needle electrode Intriguing observations from this study include the varied patterns of EF5 binding in HNSCC. Type 1 binding pattern is most similar to EF5 binding in sarcomas and brain tumors 24,25 and Type 2 binding is most reminiscent of the EF5 binding patterns described in normal human skin 30 . Using pimonidazole, similar patterns of binding have been reported 45,46 .…”
Section: Discussionmentioning
confidence: 76%
“…Based on these observations, they conclude that involucrin is a hypoxia-inducible protein, but its expression is altered by cellular differentiation. Our studies performed in human skin, which contain regions of squamous cell differentiation, suggests that "Type 2" EF5 binding is dominantly a reflection of tissue pO 2 rather than expression of other cellular proteins, state of differentiation or an artifact of elevated reductase enzymes 30 . This conclusion is supported by images of the spatial relationship between EF5 binding and CD31 staining (blood vessels) or Ki67 staining (proliferation) (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Notch1 is required by tissue hypoxia to maintain cells in an undifferentiated state (26). This is particularly relevant to melanoma, because we and others previously demonstrated that the skin is normally mildly hypoxic and that melanocytes reside in this environment (27,28). Taken together, these findings strongly suggest that the Notch1 signaling pathway can be under control of both oncogene activation and environmental conditions, although how these factors regulate Notch1 is still not fully understood.…”
Section: Introductionmentioning
confidence: 70%
“…air). Two percent O 2 was chosen to represent a physioxic environment as this concentration falls within the range of O 2 concentrations measured in healthy epidermal skin [17] and superficial epidermoid carcinomas in vivo [18]. Thus, our investigations were carried out under three different O 2 conditions (Fig.…”
Section: Introductionmentioning
confidence: 99%